Pedagogical model of visual and ocular health for educational agents. (UNA MIRADA A..., 2022)
According to statistical data from the World Health Organization (WHO), 43% of visual impairment worldwide is due to uncorrected refractive errors, with children being the most affected (12 million). For this reason, the WHO and the Pan American Health Organization (PAHO) have drawn up the Vision 20/20 Plan, the right to vision, which seeks to prevent millions of people in the world from becoming blind by the year 2020. In Medellin, according to DANE records, there were a total of 9,808 children with visual impairment. Objective: To evaluate a pedagogical model of visual and ocular health in educational agents. Methodology: Quantitative approach, with quasi-experimental field and longitudinal design. The study population was the educational agents of the Good Start Program in the city of Medellin. Results: The scores obtained in the pre-test questionnaire showed a mean difference of 64.1 (65) and in the post-test 68.6 (69) (p
Keywords: pedagogic model; preschoolers; refractive errors; education